PSYCHOLOGICAL ASPECTS OF VOLITIONAL BEHAVIOR LEADING TO CRIMINAL BEHAVIOR - Urunov Aziz Shakirovich (Modern American Journals, 2025)
This article examines the psychological pathways through which conative behavior can contribute to criminal conduct. Conative behavior, encompassing volitional and goal-directed aspects of personality such as self-regulation, persistence, decision-making, and goal orientation, plays a pivotal role in shaping individual behavioral outcomes. The study explores how deficiencies in these volitional traits, combined with environmental, social, and cognitive factors, may increase the propensity for antisocial or criminal actions. Utilizing psychodiagnostic tools, empirical observations, and statistical analyses, the research identifies critical conative mechanisms that predispose individuals to deviant behavior. The findings highlight the significance of early psychological interventions, targeted educational programs, and social support systems to strengthen volitional capacities and reduce the risk of criminal activity among adolescents and young adults.
Keywords: Conative behavior, volitional traits, criminal conduct, antisocial tendencies, psychological pathways, psychodiagnostics, juvenile delinquency, self-regulation, goal-directed behavior, preventive interventions.